2011
DOI: 10.1007/s13197-011-0407-z
|View full text |Cite
|
Sign up to set email alerts
|

Retention of nutrients in green leafy vegetables on dehydration

Abstract: The objective of the study was to investigate the influence of dehydration on nutrient composition of Amaranthus gangeticus, Chenopodium album, Centella asiatica, Amaranthus tricolor and Trigonella foenum graecum. The green leafy vegetables (GLV) were steam blanched for 5 min after pretreatment and dried in an oven at 60°C for 10-12 h. The fresh and dehydrated samples were analyzed for selected proximate constituents, vitamins, minerals, antinutrients and dialyzable minerals. Dehydration seems to have little e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 19 publications
(18 reference statements)
6
41
0
3
Order By: Relevance
“…However, lower values of 3167-3808 µg of β-carotene/100 g have been reported in IFCT, US data base and a study of Malaysia [7,17,19]. Fenugreek leaves (Trigonella foenum graecum) had β-carotene in the range of 4826-5838 µg/100 g which is nearly similar to the amount of 4230-4350 µg/100 g reported by Indian authors earlier [22,23]. Although higher values of β-carotene in fenugreek leaves (9245 ± 974 µg/100 g) were reported in IFCT [7].…”
Section: Green Leafy Vegetablessupporting
confidence: 58%
“…However, lower values of 3167-3808 µg of β-carotene/100 g have been reported in IFCT, US data base and a study of Malaysia [7,17,19]. Fenugreek leaves (Trigonella foenum graecum) had β-carotene in the range of 4826-5838 µg/100 g which is nearly similar to the amount of 4230-4350 µg/100 g reported by Indian authors earlier [22,23]. Although higher values of β-carotene in fenugreek leaves (9245 ± 974 µg/100 g) were reported in IFCT [7].…”
Section: Green Leafy Vegetablessupporting
confidence: 58%
“…The crude protein content of the leaf sample of R. mucronata was found to be 2.445 ± 0.179 % DW which is higher than the level reported in other mangrove leaves such as Suaeda maritime, Lumnitizera racemosa, Avicennia marina, Bruguiera gymnorrhiza, Sonneratia apetala and Derris trifoliata respectively 23,24 . Similar values have been reported in the edible leaves of traditional Indian medicinal plants (~ 2-3% DW) and conventional green leafy vegetables of India 25,26 .…”
Section: Results and Discussion: Proximate Composition Analysissupporting
confidence: 84%
“…Dehydrated green leafy vegetables are also rich sources of iron and β-carotene and can be used in lean season . Gupta et al (2013) also observed the influence of dehydration on nutrient composition of Amaranthus gangeticus, Chenopodium album, Centella asiatica, Amaranthus tricolor and Trigonella foenum graecum. Fenugreek (T. foenum-graecum) leaves and seeds have been used extensively for medicinal purposes.…”
Section: Bioaccessibilitymentioning
confidence: 81%